2011
DOI: 10.1108/00907321111161368
|View full text |Cite
|
Sign up to set email alerts
|

Developing learning landscapes: academic libraries driving organisational change

Abstract: Purpose -The purpose of this paper is to discuss the reasons and drivers for academic libraries affecting university strategy with regards to shaping and developing learning spaces in response to changing pedagogic behaviours. Design/methodology/approach -A review of available literature within the context of academic libraries and their position to influence and lead institutional strategic change. This theory and practice is addressed and evidenced by four case studies of university libraries in the UK. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…As far as the academic library's evolving role within its larger HE institution, Oliveira (2017) investigated the literature as it relates to libraries and student retention; however, these efforts did not extend much beyond the traditional library functions of instruction, collections, and reference. In the UK, four university libraries each influenced institutional strategies related to pedagogy and space (Appleton, Stevenson, & Boden, 2011). Other writing on the future of academic libraries did not stray far from libraries' conventional contribution areas related to student learning (Miller, 2014) or faculty research Kaufman (2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As far as the academic library's evolving role within its larger HE institution, Oliveira (2017) investigated the literature as it relates to libraries and student retention; however, these efforts did not extend much beyond the traditional library functions of instruction, collections, and reference. In the UK, four university libraries each influenced institutional strategies related to pedagogy and space (Appleton, Stevenson, & Boden, 2011). Other writing on the future of academic libraries did not stray far from libraries' conventional contribution areas related to student learning (Miller, 2014) or faculty research Kaufman (2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the value of information commons in collaborative learning, faculties are also cooperating and collaborating with librarians in developing and using information commons 12. Evidences prove that through information commons the academic libraries are actively supporting online, hybrid and collaborative learning. For example, four university libraries in UK designed and developed learning spaces so as to support collaborative learning 13 . Talvé 14 reported that internationally the library has emerged as a facility inter-woven of digital, social and aesthetic values and has generated new loci for solitary and collective learning and interaction.…”
Section: Trend Predicted: Integration Of Online Hybrid and Collaboramentioning
confidence: 99%
“…Whereas the lecture theatre reflected the teacher-led and hierarchical nature of the transmission-style of teaching and learning (Hebdige in Chism, 2002), new flexibly designed teaching spaces allow students to engage in more active and social learning (eg. Appleton, Stevenson, & Boden, 2011;Lin, Chen, & Chang, 2010;Jamieson, Fisher, Gilding, Taylor, & Trevitt, 2000;Black & Roberts, 2007). The role of the teacher evolved from being the 'sage on the stage' to the 'guide by the side' (King, 1993;Sens, 2009).…”
Section: Setting the Stagementioning
confidence: 99%
“…This has been a key driver of many library redevelopments, reflected in many innovative projects documented in the literature (eg. Beard & Dale, 2010;Appleton et al, 2011;Kay, 2009;Black & Roberts, 2007). These projects typically focus on the outcomes in library teaching and learning spaces, such as open-space flexible group work, small-group intentional collaborative, individual silent study and formal teaching and learning (Beard & Dale, 2010).…”
Section: Setting the Stagementioning
confidence: 99%